The preliminary studies of sampling point determination in accordance to heavy metals (Cd& Pb) concentration along Tabuan River / Mohammad Isa Mohamadin,Hanita Tambi & Ropisah Me - Mohamadin, Mohammad Isa; Tambi, Hanita; Me, Ropisah (2003)
A preliminary study on the condition of Tabuan River in term of heavy metals (Cadmium & Lead) concentration was conducted. The sampling activities were done twice. The first sampling is done for the purpose of surveying the concentration level of the heavy metals in the particular river. 10 Sampling locations were chosen for the first sampling activity and 10 more additional sites were added for the second sampling. The site is purposely chosen in order to establish any distribution pattern of the heavy metals along the river.